Electrotransformation on selected plant growth-promoting Rhizobacteria (PGPR) and Chromobacterium violaceum - Loke, Wai Keong; Mohd Saud, Halimi (Penerbit Universiti Sultan Zainal Abidin, 2020)
Electrotransformation was successfully transferred a 21.6 kb cosmid vector pLAFR1 into the selected Plant Growth-Promoting Rhizobacteria (PGPR) and Chromobacterium violaceum with maximum efficiency about 107 transformants/µg at electric field strength of 10kV/cm for shorter pulse length range between 4.1 to 4.4 milliseconds and about 108 transformants/µg at electric field strength of 5kV/cm for a longer pulse length range between 8.5 to 8.7 milliseconds. Longer incubation period will increase the transformation efficiency but continuing increasing the period after 20 hours will decrease the transformation efficiency.